Environmentally Friendly Roof Tiles: Comparative Study of a Mixture of Clay and Balinese Traditional Ceremonial Waste - Made Novia Indriani; I Wayan Artana; Shinta Enggar Maharani; I Putu Gede Adi Gunawan (Universitas Pendidikan Ganesha, 2025)
Clay tiles are still the main choice for building roofs even though they have a negative impact on the environment. Balinese Ceremonial Waste from Balinese ritual activities reaches 600-800 tonnes/day at certain ceremonies. This research aims to carry out conservation through roof tile material innovation mixed with Balinese Ceremonial waste. The method used is comparative and experimental with independent variables in the form of variations in the composition of Balinese Ceremonial waste and clay and dependent variables in the form of flexural strength, water seepage, water absorption and visible properties. approach laboratory experiments which aims to determine the effect of variations in the mixture of clay and Balinese traditional ceremonial waste on the quality of the roof tiles produced. The research subject is roof tile samples made from various compositions of mixed materials (clay and ceremonial waste), while participants were not directly involved because the research was material-based. The data collection method is carried out through laboratory tests on the physical and mechanical properties of roof tiles, such as compressive strength, water absorption capacity, and resistance to temperature and weather. The instruments used include compression test equipment, digital scales, drying ovens, and water absorption measuring instruments, as well as visual documentation to support observation results. The analysis results show that the use of Balinese traditional ceremonial waste as a mixture of roof tile raw materials with clay produces environmentally friendly roof tile products with competitive physical and mechanical characteristics. The implications of this research include significant environmental, social and economic aspects. Environmentally, the use of Balinese traditional ceremonial waste as a mixture of roof tiles helps reduce the accumulation of organic and inorganic waste from religious activities which have not been managed optimally.